Sialylation may be dispensable for reciprocal modulation of helper T cells by intravenous immunoglobulin. Issue 7 (2nd May 2014) - Othy, Shivashankar; Topçu, Selma; Saha, Chaitrali; Kothapalli, Prathap; Lacroix‐Desmazes, Sebastien; Käsermann, Fabian; Miescher, Sylvia; Bayry, Jagadeesh; Kaveri, Srini V.
<x xml:space="preserve">Abstract</x> Several mechanisms account for the beneficial effect of intravenous immunoglobulin (IVIg) in autoimmune and inflammatory diseases. These mechanisms include effects on the cellular compartment and on the humoral compartment. Thus, IVIg impacts on dendritic cells, macrophages, neutrophils, basophils, NK cells, and B and T lymphocytes. Several studies have emphasized that the antiinflammatory effect of IVIg is dependent on α2, 6‐sialylation of the N‐linked glycan on asparagine‐297 of the Fc portion of IgG. However, recent reports have questioned the necessity of sialylated Fc and the role of FcγRIIB in IVIg‐mediated antiinflammatory effects. In view of the critical role played by Th17 cells in several autoimmune pathologies and the increasing use of IVIg in several of these conditions, by using neuraminidase‐treated, desialylated IVIg, we addressed whether the α2, 6‐sialylation of IgG is essential for the beneficial effect of IVIg in experimental autoimmune encephalomyelitis (EAE), a Th17‐driven condition, and for the reciprocal modulation of helper T‐cell subsets. We observed no difference in the ability of IVIg to ameliorate EAE irrespective of its sialylation. Our findings thus show that sialylation of IVIg is not necessary for IVIg‐mediated amelioration of EAE or for downregulation of Th17 cells and upregulation of regulatory T cells.